9(68040)+6×2=89

Divide 680 by 40.

9⋅17+6×2=89

Multiply 9 by 17.

153+6×2=89

153+6×2=89

Subtract 153 from both sides of the equation.

6×2=89-153

Subtract 153 from 89.

6×2=-64

6×2=-64

Divide each term in 6×2=-64 by 6.

6×26=-646

Cancel the common factor of 6.

Cancel the common factor.

6×26=-646

Divide x2 by 1.

x2=-646

x2=-646

Simplify -646.

Cancel the common factor of -64 and 6.

Factor 2 out of -64.

x2=2(-32)6

Cancel the common factors.

Factor 2 out of 6.

x2=2⋅-322⋅3

Cancel the common factor.

x2=2⋅-322⋅3

Rewrite the expression.

x2=-323

x2=-323

x2=-323

Move the negative in front of the fraction.

x2=-323

x2=-323

x2=-323

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±-323

Simplify the right side of the equation.

Rewrite -1 as i2.

x=±i2(323)

Pull terms out from under the radical.

x=±i323

Rewrite 323 as 323.

x=±i(323)

Simplify the numerator.

Rewrite 32 as 42⋅2.

Factor 16 out of 32.

x=±i(16(2)3)

Rewrite 16 as 42.

x=±i(42⋅23)

x=±i(42⋅23)

Pull terms out from under the radical.

x=±i(423)

x=±i(423)

Multiply 423 by 33.

x=±i(423⋅33)

Combine and simplify the denominator.

Multiply 423 and 33.

x=±i(42333)

Raise 3 to the power of 1.

x=±i(42333)

Raise 3 to the power of 1.

x=±i(42333)

Use the power rule aman=am+n to combine exponents.

x=±i(42331+1)

Add 1 and 1.

x=±i(42332)

Rewrite 32 as 3.

Use axn=axn to rewrite 3 as 312.

x=±i(423(312)2)

Apply the power rule and multiply exponents, (am)n=amn.

x=±i(423312⋅2)

Combine 12 and 2.

x=±i(423322)

Cancel the common factor of 2.

Cancel the common factor.

x=±i(423322)

Divide 1 by 1.

x=±i(4233)

x=±i(4233)

Evaluate the exponent.

x=±i(4233)

x=±i(4233)

x=±i(4233)

Simplify the numerator.

Combine using the product rule for radicals.

x=±i(43⋅23)

Multiply 3 by 2.

x=±i(463)

x=±i(463)

Combine fractions.

Combine i and 463.

x=±i(46)3

Move 4 to the left of i.

x=±4i63

x=±4i63

x=±4i63

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=4i63

Next, use the negative value of the ± to find the second solution.

x=-4i63

The complete solution is the result of both the positive and negative portions of the solution.

x=4i63,-4i63

x=4i63,-4i63

x=4i63,-4i63

Solve Using the Square Root Property 9(680/40)+6x^2=89